Collateral impact of the COVID−19 pandemic on the use of healthcare resources among people with disabilities - Sohn, Minjeong; Koo, Heejo; Choi, Heekyoung; Cho, Hyunsan; Han, Euna (Frontiers in Public Health, 2022)
Objective We assessed the collateral impact of the COVID−19 pandemic on healthcare service use among people with disabilities. Methods We utilized the COVID−19 database from the Korean National Health Insurance Service claims from 2015 until June 2020. We included 5,850 people with disabilities and matched 5,850 without disabilities among those who were neither tested nor diagnosed with COVID−19. We used a quasi–experimental setting with a COVID−19 outbreak as an external event in a difference–difference estimation with matching controls. Results Participants with disabilities recorded a larger decrease in the number of claims for total services (2.1 claims per 5 months) upon the COVID−19 pandemic's onset compared to those without disabilities (1.6 claims), and the difference–in–difference estimates were statistically significant (0.46 claims). The decline was driven by outpatient and emergency visits. The extent of the decline was large for the severe disability group overall. By disability type, those with a physical disability showed a statistically significant decline in the number of claims. Conclusion The COVID−19 pandemic has had a collateral impact on people with disabilities' use of healthcare services. Continued assessment is needed regarding whether the collateral impact has been sustained or is following a different path.